First-in-human dose: current status review for better future perspectives - Mishra, Archana; Sarangi, Sudhir Chandra; Reeta, Kh (European journal of clinical pharmacology, 2020)
Aim The aim of this article is to understand the pros and cons of various methods involved in first-in-human (FIH) dose calculation and act decisively in dose escalations when calculating the maximum tolerated dose. Subjects and methods We reviewed early phase clinical trials for methods of FIH dose and dose-escalation steps and discuss them in line with existing guidelines. We also reviewed the clinical trial registry to recognize trends in trial registration in recent years and after a massive failure in a few trials. Results Phase 1 trials of TGN 1412 and BIA10-2474 would always be remembered as catastrophes for pharmaceutical development plans. Quite often than not, healthy human volunteers are the guinea pigs in this stage of drug development. And, the most important aspect of designing an early phase study is deciding upon the dose to be started with, apart from the selection of cohort and escalation steps. The common principles used for FIH dose calculation include no observed adverse effect level, minimum anticipated biological effect level, pharmacologically active dose, pharmacokinetic/pharmacodynamic approach, and similar drug comparison approach. Conclusion Early phase clinical trials are basically foundation stones on which lies the entire onus of the later stages of development. Deciding FIH dose is a crucial step that necessitates the incorporation of detailed data from the preclinical stages and application of the most conservative approach for the safety/benefit of the volunteers in these studies.